Efektivitas Penggunaan Media Latar Terhadap Keaktifan Belajar Peserta Didik Kelas III MI Ulumul Quran Ali Bin Abi Thalib Surakarta - Dewi Masitoh; Anggit Grahito Wicaksono; Ema Butsi Prihastari (CV. ITTC INDONESIA, 2023)
This study aimed to determine the effectiveness of using LATAR media (Lagu Bangun Datar) on student learning activity in class III MI Ulumul Quran Ali Bin Abi Talib Surakarta in 2022/2023 academic year. The research method used in this research was descriptive quantitative research design with One Group Pretest-Posttest Design. The subjects in this study were students in class III MI Ulumul Quran Ali Bin Abi Talib Surakarta in 2022/2023 academic year, totaling 28 students. Data collection techniques were through questionnaires, documentation, and observation. Instrument test were carried out in class III SD Kanisius Pucangsawit with a total sample of 28 students. The data analysis technique used was the data normality test with Kolmogorov Smirnov formula. The hypothesis tests was to use the Paired Sample T-test and the N-Gain test. The results showed that based on the results of the N-Gain test, the pre-test and post-test scores were 0.59 and include in the moderate category with a percentage of 59%. So, it could be concluded that the use of LATAR Media (Lagu Bangun Datar) had a fairly effective effect on student learning activity inf class III MI Ulumul Quran Ali Bin Abi Talib Surakarta in the 2022/2023 academic year.